Promoting Democracy in Prosecution - Gold, Russell M. (2011)
Voters were meant to check prosecutors’ decisions, but that check has eroded because voters lack the information necessary to cast meaningful votes in prosecutor elections. Voters’ lack of an effective political check on prosecutors causes two related problems: (1) inefficient allocation of prosecutorial resources and (2) divestment of democratic sovereignty from the people. Prosecutors currently need not consider expenditures for incarceration or public defense because voters never see these costs and thus cannot hold their prosecutors accountable for them. Accordingly, these costs become an externality in the prosecutorial decision-making process, causing prosecutors to spend resources in socially inefficient ways. To reinvigorate the political check on prosecutors, this Article proposes requiring state and local prosecutors to disclose costs of all prosecuted cases and all cases not prosecuted in which an arrest was made and sufficient evidence existed. Such disclosures would sweep broadly to include prosecutors’ wages, public defense costs, and incarceration costs in cases resulting in a conviction. Voters would then have concrete, monetized evidence of prosecutorial priorities. This greater information flow would allow voters, through the ballot box, to meaningfully supervise their prosecutors’ exercise of delegated sovereign authority. Knowing that voters wield this information, prosecutors would then internalize this externality by taking these previously disregarded costs into account when they determine whether to charge crimes, what crimes to charge, and what sentences to recommend. Creating a mechanism that urges prosecutors to consider this broader set of costs would promote a more socially efficient outcome. Finally, this Article considers what an efficient allocation of prosecutorial resources might look like. It postulates that many constituencies would rather spend less on small-scale drug prosecutions to save cash-strapped state budgets